Medicaid and the limits of state health reform - Sparer, Michael S. (Temple University Press, 1996)
A critical look at state-dominated health care.
Keywords: Health care reform -- United States -- States.; Medicaid.; Medical policy.; Health planning.; Medical care.; Social control.; Non-governmental organizations.; Health services administration.; Public welfare.; Social sciences.; Health care reform.; Economics.; Sociology.; Health Policy; Medical Assistance; Government; Health Planning; Delivery of Health Care; Legislation as Topic; Public Policy; Social Control, Formal; Health Care Economics and Organizations; Health Care Quality, Access, and Evaluation; Organizations; Patient Care Management; Public Assistance; Social Sciences; Health Care Reform; State Government; Medicaid; Social Control Policies; Anthropology, Education, Sociology and Social Phenomena; Health Services Administration; Financing, Government; Policy; Financing, Organized; Economics; Sociology; Patient Care; Services de santé -- Réforme -- États-Unis -- États.; Politique sanitaire.; Institutions politiques.; Santé publique -- Planification.; Prestation de soins.; Contrôle social.; Organisations non gouvernementales.; Services de santé -- Administration.; Aide sociale.; Sciences sociales.; Services de santé -- Réforme.; Aide de l'État.; Économie politique.; Sociologie.; Soins médicaux.; governments (administrative bodies); welfare services.; social sciences.; federal aid.; economics.; sociology.; HEALTH & FITNESS -- Health Care Issues.; MEDICAL -- Public Health.; MEDICAL -- Health Policy.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Diseases.; MEDICAL -- Health Care Delivery.; MEDICAL -- General.; Health care reform -- U.S. states; United States